Platelet Membrane Potential: Simultaneous Measurement of diSC3(5) Fluorescence and Optical Density - Pipili, Eva (Thrombosis and Haemostasis, 1985)
The role of membrane potential in the activation of human platelets by thrombin, ADP and PAF was assessed, using the fluorescent probe diSC3(5). Thrombin, ADP and PAF transiently depolarised the platelet membrane by 6-8 mV from its resting level (—70 mV). This depolarisation had a similar time course to that of shape change. The ionophores valinomycin and gramicidin hyperpolarised and depolarised the platelets respectively but did not activate them. In contrast, exposure of platelets to high K+ media both depolarised and caused them to change shape. Removal of Na+ from the suspension media abolished the depolarisation induced by thrombin, ADP and PAF but the platelets under these conditions were still capable of changing shape and aggregating. This result indicates that the observed depolarisation depends on Na+ fluxes. Amiloride or tetrodotoxin did not mimic the effect of Na+ removal suggesting that any Na+ movement involved does not go through the classic “Na+ channel”. Thrombin, ADP and PAF still depolarised the platelet membrane in the absence of added Ca++. Under these conditions, however, the membrane did not repolarise. It is evident that all three agents, thrombin, ADP and PAF, change the membrane potential of human washed platelets through a similar mechanism and this change seems to be a consequence of stimulus-receptor interaction (and platelet activation?). A causal relationship however between these events cannot be clearly shown.
Keywords: Platelet activation; Tissue plasminogen activator; Membrane potential; Fluorescent dye Summary